EXTRACTION OF LEAD FROM GALENA CONCENTRATES USING FLUOSILICIC ACID AND PEROXIDE - Dessy Amalia; Yunita Ramanda; Maryono Maryono (Indonesian Mining Journal, 2017)
A study on lead extraction from lead concentrate had been conducted. Galena is usually associated with other sulfide ores such as sphalerite.The lead concentrate was able to be extracted and purified into its metal through a leaching process using a selective solvent of fluosilicic acid (H2SiF6). Parameters used in this process include ratio (dose) of reactant (H2SiF6:H2O2), temperature (without heating; 30; 50; 70; 80; and 90°C) and particle size (-100+150#, -150+200#, -200+325, dan -325#).The best extraction was achieved using the particle size of -325 mesh. The amount of extracted lead was increased due to the rise of temperatureand dose of fluosilicic. The amount of peroxide addition was determined by its optimum influence on the lead extraction because its excess would produce PbSO4. The influence of H2SiF6 and H2O2doses was calculated using ANOVA.